1993
DOI: 10.1063/1.109973
|View full text |Cite
|
Sign up to set email alerts
|

Below band-gap electroabsorption in bulk semi-insulating GaAs

Abstract: Electroabsorption measurements of bulk semi-insulating GaAs using a pulsed applied voltage are presented for the wavelength range 890–920 nm and compared with results of the same measurement using a dc applied voltage. In the latter case, field inhomogeneities in the GaAs gives a spatially dependent absorption which thwarts extraction of the absorption coefficient versus electric field. We circumvent this problem by transiently measuring the absorption during a pulsed bias voltage when the field in the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…deep donor centers and produce a neutralization effect [53] . If the electron capture rate is higher than the electron emission rate near ec, then the leakage current through a reverse biased Schottky contact may create a case similar to An doped Si where a quasineutral region is formed [54] .…”
mentioning
confidence: 99%
“…deep donor centers and produce a neutralization effect [53] . If the electron capture rate is higher than the electron emission rate near ec, then the leakage current through a reverse biased Schottky contact may create a case similar to An doped Si where a quasineutral region is formed [54] .…”
mentioning
confidence: 99%
“…26 Similar reports for de biased semiconductor switches have also been described in the literature. 27 So proceeding with the low frequency stability analysis, we ignore all of the nonlinear terms in w, and rewrite Eq. (7) in the following form: (8) where the coefficients Pi and Qi can be expressed in terms of the various Bi and Ci terms already defined.…”
Section: Ill Results and Discussionmentioning
confidence: 99%
“…We believe the most likely explanation to be the formation and propagation of streamer-like phenomena. The existence of streamer-like domains in semiconductors was first proposed by D'yakonov and Kachorovskii [3], and several workers have suggested that they might be responsible for the "lock-on" effect observed in GaAs [4], [5].…”
mentioning
confidence: 99%